A Study on Social Intelligence and Life Satisfaction among Higher Secondary Students - Selvam, S.K. Panneer (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Human society as we know it could not exist without minds and selves, since all its most characteristic features presuppose the possession of minds and selves by its individual members; but its individual members would not possess minds and selves if these had not arisen within or emerged out of the human social process in its lower stages of development-those stages at which it was merely a resultant of, and wholly dependent upon, the physiological differentiations and demands of the individual organisms implicated in it. There must have been such lower stages of the human social process, not only for physiological reasons, but also for minds and selves. Consciousness and intelligence, could not otherwise have emerged; because, that is, some sort of an ongoing social process in which human beings were implicated. All these relationships indicate that life satisfaction is a multidimensional concept. There are various resources which have found the relationship between life satisfaction and life involvement among the variety of population.